OP0319 Genetically Determined Mannose-Binding Lectin Deficiency Increases Risk of Nephritis in Danish Patients with Systemic Lupus Erythematosus. (23rd January 2014) - Jacobsen, S.; Tanha, N.; Troelsen, L.; Hermansen, M.-L. F.; Kjær, L.; Faurschou, M.; Garred, P.
Abstract : Background: Mannose-binding lectin (MBL) is involved in the processing of apoptotic debris; deficiencies in this mechanism are strongly associated with autoimmunity, including systemic lupus erythematosus (SLE) with nephritis, i.e. lupus nephritis (LN). Objectives: To determine if the genetically determined state of MBL-deficiency confers an increased risk of LN in SLE. Methods: SLE patients attending a Danish tertiary rheumatology center were genotyped in exon 1 of the MBL2 gene at codon 52, 54, and 57 for single-base substitutions named O versus the wildtype allele A. MBL2 genotype thus comprised genotypes A/A, A/O, and O/O (MBL deficient). Development and histological class of LN was looked for from the time fulfillment of the ACR 1987 classification criteria for SLE until end of follow-up. Development of end-stage renal disease (ESRD) was looked for from time of LN to end of follow-up. Cox regression analyses were controlled for gender, age, race, and immunosuppresants. Results: Of the 171 patients included in the study, 91 percent were female and 92 percent of Caucasian descent. The median age at SLE onset was 29 years (range 11-72 years). The median follow-up from time of SLE classification to development of LN or end of follow-up was 5.7 years (range 0-34 years) with a total of 1165 patient-years. LN developed in 94 patients and among these ESRD developed in 16 patients during 1556 patient-years. The prevalence of A/A, A/O, and O/O MBL producers was 99 (58%), 60 (35%) and 12 (7.0%), respectively. Conclusions: The finding of a 2.6-fold increased risk of LN among MBL deficient SLE patients supports the notion that deficiencies in innate immunity components involved in removal of apoptotic remnants may promote immunecomplex mediated manifestations of SLE. ESRD was not associated with MBL deficiency indicating its greater importance in early events of LN. These findings enhance our understanding of the pathogenesis of SLE. Furthermore, the relatively high background prevalence of MBL deficiency and the fact that 10 out of 12 such SLE patients eventually developed LN, also indicates that MBL genotyping may have a place in clinical risk stratification of SLE patients. Acknowledgements: Danish Rheumatism Association, Novo Nordisk Foundation, Rigshospitalets Research Fund Disclosure of Interest: None Declared